The Value of Self-Reported Costs in Repeated Investment Decisions. - Fellingham, John C.; Young, Richard A. (The Accounting Review, 1990)
Describes a model where an endogenous demand for cost reports exists, and characterizes optimal contracts. Achievement of cost report perspective; Necessary conditions for communication; Incorporation of cost reports within an optimal contract; Costs and benefits of communication-based two-period contracts.